Music and Erotic Agency – Sonic Resources and Social-Sexual Action - Tia DeNora (Transposition)
How does the cultural configuration of being and body happen? Just how are cultural products mobilized and how do texts, images, sonic structures and representations inform and thereby “get into” action? These are key questions for cultural studies, sociology and social psychology. They have so far not been addressed head on, and they by no means entail a mere “empirical implementation” of an otherwise already complete theorization of agency. In this article, I suggest that a good theory of agency can be developed through specific considerations of particular social realms, and with reference always to particular cultural materials. To this end, after some initial theoretical clarification of the links between culture, nature and social agency, I focus on the erotic, in order to pursue a more general concern with the interrelationship of expressive media and social agency.1 More specifically, I consider the question of how erotic agency maybe “musically composed”2, by which I mean how agency may take shape with reference to musical media.